Enhancing critical thinking in Ugandan secondary school: Teacher professional development action research - Giacomazzi, Mauro; Zecca , Luisa; Maggioni , Liliana (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2023)
Critical thinking is recognized as key in any society. However, the Ugandan system of education is not helping students to become critical thinkers; the education is superficial and uncritically based on rote learning. The main objective of this study was to investigate and document how Ugandan secondary school teachers could be supported in explicitly pursuing the goal of fostering students’ critical thinking. This professional development action research showed that the instructional support coaching system contributed to enhancing the teachers’ professional and pedagogical capacity, led them to transform their instructional planning process, and shifted their beliefs with regard to curricula and learning theories.